Asuhan Keperawatan Luka Efektivitas Madu Terhadap Penyembuhan Luka Diabetikum Pada Penderita Diabetes di Panti Sosial Bina Daksa Budi Bhakti 2 - Kurniawan, Rizqi; Intan Suri, Oryza (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Background: Diabetes mellitus is a chronic metabolic disease that can lead to complications such as diabetic ulcers, chronic wounds that require intensive care. Purpose: To evaluate the effectiveness of honey as a dressing in the healing of diabetic wounds. Research Methods: A case study on two patients with type II diabetes mellitus at the Bina Daksa Budi Bhakti 2 Social Care Center, with honey intervention for seven days and periodic observation. Research Results: Indicated improvement in wound condition, reduced exudate, and increased granulation tissue, accompanied by decreased blood sugar levels. Honey has antimicrobial, anti-inflammatory properties and supports autolytic debridement that accelerates the healing process. Conclusion: Honey is effective as an alternative therapy in the care of diabetic wounds and can improve the quality of nursing care.